An Implementation of Medical Image Retrieval Using Convolution Neural Network - K. Menaka, Dr.P.D.R.Vijayakumar (International Journal of Advanced Science and Technology, 2020)
The proposed research paper implemented with a system provided detection system with tag matching with image processing using DCM image retrieval method format. This method executes the tag matching directly with an image by passing the identification of the parameter values and utilize the classes as queries. With the method of utilizing the DCM image to process of removing the powerful characteristic for the explanation of tag in the image objects. The characteristics used to compare the capable of capturing the common characters in the image to tag the objects under on tag of the images. To illustrate the efficiency of the proposed research work, we utilized a collection of 22 classes of database and we train all the classes by tags and category of an image by deep learning algorithm to gain the rate of retrieval of image using MATLAB graphical user interface (GUI).